The moving body (le corps poétique) : teaching creative theatre - Lecoq, Jacques; Carasso, Jean-Gabriel; Lallias, Jean-Claude (Theatre makers, 2019)
"Jacques Lecoq was one of the most inspirational theatre teachers of our age. In The Moving Body, Lecoq shares with us first-hand his unique philosophy of performance, improvisation, masks, movement and gesture, which together form one of the greatest influences on contemporary theatre. Neutral mask, character mask and counter masks, bouffons, acrobatics, commedia, clowns and complicity: all the famous Lecoq techniques are covered in this book - techniques that have made their way into the work of former collaborators and students including Dario Fo, Ariane Mnouchkine, Yasmina Reza and Theatre de Complicite. The book contains a foreword by Simon McBurney and an afterword by Fay Lecoq, Director of the International Theatre School in Paris"--